1995
DOI: 10.1590/s0036-46651995000500007
|View full text |Cite
|
Sign up to set email alerts
|

Serological findings during a measles outbreak occurring in a population with vaccine coverage

Abstract: From March 1991 to April 1992, serum samples for IgM detection were collected from 112 clinical measles cases reported to the Health Department of Niterói, State of Rio de Janeiro. The positivity exceeded 90% for specimens collected from the 5th to the 29th day after the onset of the disease. After day 30 a decline in IgM detection was observed, although positivity has been detected up to 90 days after the onset of the symptoms. Forty-four patients (48.9%) with an IgM response had a history of prior measles va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…From the 92 cases received from ES in the years of 1992 and 1994, we had the same number of positives for measles and B19. In a previous study of an outbreak of exanthem in Niterói, RJ during 1991 we obtained 80% of laboratory confirmation of 112 measles reported cases 19 . In that study no cases with anti-B19 IgM were found and rubella was diagnosed in only four cases.…”
Section: Discussionmentioning
confidence: 85%
“…From the 92 cases received from ES in the years of 1992 and 1994, we had the same number of positives for measles and B19. In a previous study of an outbreak of exanthem in Niterói, RJ during 1991 we obtained 80% of laboratory confirmation of 112 measles reported cases 19 . In that study no cases with anti-B19 IgM were found and rubella was diagnosed in only four cases.…”
Section: Discussionmentioning
confidence: 85%
“…The former could be related to the higher proportion of virus antibody negative indi-viduals in younger age groups. The later resulted probably from the timing of specimen collection, since test sensitivity is known to be lower in the early period of the disease, when antibody levels are not high enough to be detected [12,29,30].…”
Section: Discussionmentioning
confidence: 99%